2018
DOI: 10.4236/oalib.1104501
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Skin Whitening among Female University Students in Northeastern Nigeria

Abstract: Introduction: Skin whitening is the act of brightening the skin complexion by using substances that are applied on the skin or administered into the body by other means. The use of skin whitening agents has its drawback in terms of causing harmful effects such as skin disorders like depigmentation, rashes, pimples, discolorations, kidney damaged, cancers, neurological and psychiatric disorders depending on how the agents for skin whitening are used. Objective: The paper examines the knowledge, attitude and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
2
12
0
1
Order By: Relevance
“…Respondents who were highly concerned with their appearance reported more misuse than those who reported a lowmoderate concern. This finding was similar to those of a study [28], which reported that (56.0%) of participants considered skin whitening to be a factor in improving their aesthetic appearance. Another factor in our study was education.…”
Section: Discussionsupporting
confidence: 91%
“…Respondents who were highly concerned with their appearance reported more misuse than those who reported a lowmoderate concern. This finding was similar to those of a study [28], which reported that (56.0%) of participants considered skin whitening to be a factor in improving their aesthetic appearance. Another factor in our study was education.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the participants knew that skin-whitening products can cause adverse side-effects (88%). In alignment with study conducted in University of Al-gezira (7) in Sudan, and another one in Nigeria (10) . That indicates that people generally know that skin-whitening can cause adverse side-effects.…”
Section: Discussionsupporting
confidence: 66%
“…(81.8%) of the participants had poor knowledge regarding skin-whitening agents .Which is even a higher percentage than what was found in university students in Nigeria (56.1%). (10) This might be due to the fact that Nigeria is a leading country in manufacturing skin-whitening products, unlike Sudan, therefor knowledge about this matter is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists can play an important role towards minimizing adverse drug reactions (AD through promoting proper counseling, improve the situation [16]. About 38% of the users referred to leaflet to obtain information it was only about 21% in a Nigerian study [17] ( Table 2).…”
Section: Studies Conducted In Various Countries Includingmentioning
confidence: 99%
“…Pharmacists can play an important role towards minimizing adverse drug reactions (ADRs) through promoting proper counseling, and the situation [16]. About 38% of the to obtain information, but it was only about 21% in a Nigerian study [17] Once or twice daily use of clobetasol cream was as reflected in a previous study [15] (Fig. 2).…”
Section: Studies Conducted In Various Countries Includingmentioning
confidence: 99%